La Dolce Vite. L'apicoltura come intervento di educazione assistita con le persone disabili - Prestini, Giovanni (Traiettorie inclusive - Open Access, 2017)
A case of Animal Assisted Education with bees by the Pyramid Cooperative of Arcore (MB), which has started an innovative project with disabled people to teach them how to breed bees, extract honey (called "La Dolce Vite"), pack and sell it. It has brought important results in terms of psychomotor skills, self-esteem, awareness, positive self-vision.